(untitled) (PerCursos, 2021)
Márcia Wayna Kambeba, is an indigenous woman of the Kambeba people, born in the upper Solimões region and now living in the state of Pará. Márcia is an award-winning writer, author of books and poetry published in Brazil, Europe and the United States. Artist, activist and teacher. Márcia has a master’s degree in Geography from the Federal University of Amazonas, her productions are crossed by the indigenous struggle and supported by the cosmology of her people. In her work, Márcia recovers narratives from her ancestors, brings up the enchanted and the knowledge of the forest, provoking reflections on the epistemic perspectives of indigenous peoples and women. Márcia Kambeba is also a candidate for councilor for the Socialism and Freedom (PSOL) in Belém in this 2020 election - considered by the indigenous movement as a historic election due to the number of indigenous candidates, men and women, running for municipal positions. The presence of women in the political spaces created by the indigenous movement has grown in recent years, and their massive presence in this election shows the willingness and courage of these women to face the power structures established with colonial bases in Brazil. In this interview, Marcia Kambeba tells about her life trajectory, reflects on the struggles of indigenous women and their relationship as feminism, talks about indigenous ways of doing politics and about possible bridges with party politics, addresses issues such as territoriality, circular time and importance of narrative for indigenous peoples, and the contradictions of city life.